Redressing the asymmetries of international investment treaty regime from a South African perspective - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
The recent investment policy shift, by the South African government, including, termination of bilateral investment treaties with some developed countries, is illustrative of the continued discontent by most developing countries with the status quo in the realm of international investments agreements (IIAs) regime. Balancing governments' sovereign right to implement domestic policies, in order to achieve socio-economic goals, for overall sustainable development, and the corresponding duty to protect foreign investments within the host state seems perpetually elusive, within the current bilateral investment treaty (BIT) regime. The parallel rising of free trade agreements (FTAs) incorporating investment chapters to BITs and the withdrawal from international investment arbitration by some countries, is symptomatic of continued disgruntlement with the current investment regime. South Africa is amongst the front runners of this discontentment and has voiced its concerns with the system, by cancelling some of its BITs and substituting same with adopting a new domestic investment regime instead, the investment Act of 2015. This study analyses the government's policy shift, with a view to find the extent to which the current BIT regime constrained the government's policy space towards economic transformation. This is achieved by analysing the substance and objective of the policy reform as against the international standards. Consequently, after probing the global investment regime and more in particularly the country's economic and political architecture, the study found that although South Africa's investment policy shift was labelled 'drastic and regressive' by critics, the latter is rational when subjected to substantive approach to the rule of law. Author however, concludes that it is the implementation thereof that is disproportional, as the same objectives underpinning the policy reform can be achieved through a less contentious approach. Finally author suggests a renegotiation of a model BIT as a less onerous and proportionate tool, to achieve the balance sought, and recommends policy options for enhancing international investment regime to address the challenges identified.